2011
DOI: 10.2166/wh.2011.148
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of roof-harvested rainwater in the West Bank, Palestinian Authority

Abstract: Rain harvesting is becoming more common in the Palestinian Territories as a result of drinking water scarcity. Although it might pose serious human health risk, this water is being consumed without treatment in many areas of the West Bank. The present study evaluates the physicochemical and microbial quality of harvested rainwater that is used as potable water in the West Bank. Samples from roof-harvested rainwater storage tanks (n ¼ 42) were collected in summer (SS) 2006/winter (WS) 2007. Physicochemical para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…The occurrence of Aeromonas in untreated drinking water is much higher than in treated drinking water, Table 4 (Borrell et al, 1998;Carvalho et al, 2012). Also, roof-harvested drinking water showed an incidence of Aeromonas that ranged between 7-32% (Daoud et al, 2011;Dobrowsky et al, 2014;Ahmed et al, 2014). These bacteria have also been isolated in mineral bottle and sached-packed drinking water with unreported clinical impact (Korzeniewska et al, 2005b;Venieri et al, 2006;Ahmed et al, 2013).…”
Section: In Drinking Watermentioning
confidence: 99%
“…The occurrence of Aeromonas in untreated drinking water is much higher than in treated drinking water, Table 4 (Borrell et al, 1998;Carvalho et al, 2012). Also, roof-harvested drinking water showed an incidence of Aeromonas that ranged between 7-32% (Daoud et al, 2011;Dobrowsky et al, 2014;Ahmed et al, 2014). These bacteria have also been isolated in mineral bottle and sached-packed drinking water with unreported clinical impact (Korzeniewska et al, 2005b;Venieri et al, 2006;Ahmed et al, 2013).…”
Section: In Drinking Watermentioning
confidence: 99%
“…Apart from these, other studies assessing the quality of harvested rainwater are available for different parts of the world: Lye (1987) in Kentucky-USA, Fujioka et al (1991) in Hawaii, Coombes et al (2000) in NSW-Australia, Handia (2005) in Zambia, Hernandes and Vieira (2005) in Southeast Brazil, Peters et al (2008) in Bermuda, Ahmed et al (2009) in SEQAustralia, Daoud et al (2011) in Palestine, Gikas and Tsihrintzis (2012) in Northeast Greece, Shuster et al (2013) in Ohio-USA, Van der Sterren et al (2013) in Sydney, and Dobrowsky et al (2014aDobrowsky et al ( , 2014b in WC-South Africa. Finally, a summary of the reports on the chemical and biological quality of harvested rainwater tanks can be found in Kwaadsteniet et al (2013).…”
Section: Quality Threat 2: Lack Of Maintenance Periodic Cleaning Andmentioning
confidence: 99%
“…In England and Wales the majority of PWS are springs, boreholes and wells and a review conducted between 1992 and 2003 identified PWS as the source of 13 outbreaks of human campylobacteriosis [100]. Rainwater tanks specifically have been identified as a source of contamination in reported outbreaks of campylobacteriosis [101,102,103]. One study conducted in Australia found that 44% (12/27) rainwater tanks used for drinking water contained Campylobacter spp.…”
Section: Water Sources/surface Watersmentioning
confidence: 99%